Causes and Impacts of Internal Migration in Quality of Life (In the Reference to Birendranagar Municipality Ward no-2, Surkhet) - Paudel, Balkrishna (NPRC Journal of Multidisciplinary Research, 2024)
Background: This study explores the causes and consequences of internal migration in Nepal, specifically focusing on Birendranagar Municipality, Surkhet. It investigates the impacts of migration on both origin and destination areas, highlighting issues related to education, healthcare, employment, and socio-economic dynamics. Objective: The primary objective of the study is to explore the factors driving internal migration in Birendranagar Municipality and its subsequent effects on local communities, with a focus on challenges faced in both rural and urban contexts. Methods: The research employs a descriptive design and utilizes a simple random sampling method to select 56 households from a total of 367 migrant households in Birendranagar-2. Data collection was done through structured interviews, providing primary information for analysis. Findings: The study reveals that poor infrastructure, lack of employment opportunities, and social insecurity in rural areas are key drivers of migration. In contrast, urban areas face issues such as overcrowding, strain on public services, and cultural shifts. Additionally, migration is influenced by physical difficulties, climatic conditions, Nepalese civil war, and scarcity of essential facilities. Conclusion: The study emphasizes the need for improved infrastructure in rural areas and the development of policies to manage migration in a sustainable manner. The rapid population increase in urban areas presents significant challenges for local governments and development programs. Novelty: This research provides new insights into the socio-economic impacts of internal migration in Surkhet, offering recommendations for better migration management strategies and highlighting the role of local government and community awareness in addressing these issues.